2020
DOI: 10.31393/morphology-journal-2020-26(1)-02
|View full text |Cite
|
Sign up to set email alerts
|

Change of anthropometric indicators in qualified young women volleyball players during the annual training macrocycle

Abstract: Determining the indicators of the external body structure, which are inherent in highly qualified athletes of a particular sport during the annual training macrocycle, can be reliable markers in sports selection. The aim of the work is to determine the differences of anthropometric dimensions in qualified young women volleyball players at the beginning of the preparatory period and at the end of the competitive period of the annual training cycle. We examined 36 young women volleyball players of the section of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…The average arm length of the examined volleyball players (79.4 cm) is comparable to results reported by other researchers (Sarafyniuk et al 2020), and larger compared to basketball players . The width of the shoulders (39.6 cm) and pelvis (28.1 cm) of study participants is rather average compared to elite players reported by other studies (39.2-40.9 cm and 27.6-33.1 respectively; Papadopoulou 2003;Carvajal et al 2015).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The average arm length of the examined volleyball players (79.4 cm) is comparable to results reported by other researchers (Sarafyniuk et al 2020), and larger compared to basketball players . The width of the shoulders (39.6 cm) and pelvis (28.1 cm) of study participants is rather average compared to elite players reported by other studies (39.2-40.9 cm and 27.6-33.1 respectively; Papadopoulou 2003;Carvajal et al 2015).…”
Section: Discussionsupporting
confidence: 86%
“…These studies have revealed that, compared to students not actively involved in sport activities, volleyball players tended to be taller, while their circumferences of the arm and crus, most of the chest dimensions, body density, and lean body mass exhibited higher values. The above changes in physical development and fitness levels may be caused by volleyball training, resulting in the overall increase in shoulder width, circumferences of the chest and tensed shoulder, thigh and calf in young female volleyball players during one year training period (Sarafyniuk et al 2020). The influence of the volleyball activities on anthropometric characteristics appears to be greater compared to other game sports.…”
Section: Introductionmentioning
confidence: 99%